Clinical Effect of Addition of Beraprost Sodium to Pioglitazone Treatment on the Blood Glucose Levels in Patients with Type 2 Diabetes Mellitus - Chen, T.; Kusunoki, M.; Sato, D.; Tsutsui, H.; Nakamura, T.; Miyata, T.; Oshida, Y. (Experimental and Clinical Endocrinology & Diabetes, 2013)
In recent years, the number of patients with type 2 diabetes mellitus caused by insulin resistance has continued to increase in Japan. Insulin resistance is considered to be closely related to the risk of cardiovascular diseases and atherosclerotic diseases, represented by arteriosclerosis obliterans (ASO). Therefore, improvement of insulin resistance is one of the important strategies in the treatment of type 2 diabetes mellitus. At present, α-glucosidase inhibitors, incretin-related drugs, and thiazolidinediones are among the most important oral hypoglycemic drugs used to improve insulin resistance. In this study, the effect of beraprost sodium, a prostaglandin I2 derivative, in the treatment of type 2 diabetes mellitus was investigated. In type 2 diabetic patients with ASO who were under treatment with pioglitazone, additional treatment with beraprost sodium exerted a significant synergistic effect in reducing the serum HbA1c levels as compared to treatment with pioglitazone alone. This result indicates that concomitant administration of pioglitazone and beraprost sodium may be useful in the treatment of diabetes mellitus.
Keywords: beraprost sodium; pioglitazone; HbA1c; type 2 diabetes